Anaphylaxis: the current state of knowledge - Czyż, Rafał; Leśkiewicz, Marcin; Czyż, Izabela (Journal of Education, Health and Sport, 2018)
Anaphylaxis is a severe, life threatening, generalised or systemic hypersensitivity reaction. In the last decade there has been a significant increase in the frequency of anaphylactic reactions in all age groups and all regions of the world. It is estimated that about 0.3% of the European population experience anaphylaxis at some point in their lives. In connection with the above, this article summarizes current information about anaphylaxis. The following aspects were discussed: definition, epidemiology of disease, pathomechanism, triggers, signs and symptoms, clinical criteria for the diagnosis, treatment and preventive activities.